A Preliminary Understanding of Search Words used by Children, Teenagers and Young Adults in Seeking Information about Depression and Anxiety Online. Issue 4 (2nd October 2018) - Campbell, Andrew J.; Ridout, Brad F.; Linden, Melina; Collyer, Brian; Dalgleish, John
Abstract: There is a dearth of research related to mental health search word literacy for under 25's. The knowledge of a young person's mental health information search practices is piecemeal, derived from general search literacy studies. A young person's access to mental health information online is highly due to the level of stigma and poor mental health literacy surrounding depression and anxiety. This study explored what search words young people aged 5–26 (N = 630) used to identify information and/or help for depression and anxiety. The research hypothesis was supported that those under age 13 would have a more limited use of "disorder" phrases (compared to "thoughts/feeling" phrases) in their search for mental health information related to their symptoms. All age and gender groups were as likely to use thoughts/feelings terms, however, those over 13 years were almost three times more likely to combine their thoughts/feelings terms with disorder terms, compared to those less than 13 years. Results give indication that search engine optimization by expert mental health sources should take into account feeling-based vocabulary used by specific age and gender groups, in order to guide these young people to authoritative mental health information.